A comparative analysis of the mesoscale thermohaline features across subarctic frontal zones in the Northern Hemisphere. (February 2023) - Hu, Rou; Li, Ziguang; Wu, Dexing
Abstract: Mesoscale eddies and their thermohaline features across the two subarctic frontal (SAF) zones, the Oyashio Extension (OE) and the Gulf Stream (GS), in the Northern Hemisphere are investigated and compared using both satellite-based observations and Argo float data. Our results show that the thermohaline properties (temperature, salinity and associated density) induced by mesoscale eddies have significant differences between the south and north sides of each SAF zone. The relationships between the sea surface height anomaly (SSHA) and the sea surface temperature anomaly (SSTA), called the H-T amplitude relationship, are examined and used to depict the mesoscale sea surface characteristics. In both the OE and GS regions, SSTAs on the north sides of the SAFs are more sensitive to the SSHA than that on their southern sides, and this sensitivity is stronger in the GS than in the OE. It is found that in the OE, the difference in the H-T amplitude relationships between the north and south sides is mainly due to the thermal expansion coefficient, which is contingent on the ambient sea surface temperature. In the GS, the difference between the north and south sides in the H-T amplitude relationships is mainly due to the change of the vertical profiles of mesoscale eddies, which are related to the ambient meridional density front. Highlights: The thermohaline features of mesoscale eddies are significantly different between the north and south sides of the SAFs. The mesoscale H-T amplitude relationship is more sensitive on the north side of the SAFs than that of south side. The difference of the H-T amplitude relationship in the OE is attributed to background SST induced thermal expansion. The difference of the H-T amplitude relationship in the GS is attributed to the vertical structure of mesoscale eddies.